Incident Numbers of Toxic Anterior Segment Sydrome and Posterior Capsular Opacification in Patients Post Senilic Cataract Operation at Jec-Orbita Eye Clinic Makassar 2022 - Feryansyah Akhbar Syamsir; Sri Irmandha Kusumawardhani; Siti Suleha Umar; Zulfikri Khalil Novriansyah; Diah Tantri Darkhutni (Sean Institute, 2024)
Cataracts are defined as an opacification process in the lens that prevents light from entering the deeper parts of the eye. Surgery is currently the definitive treatment for cataracts to optimize the patient's visual function. However, despite the benefits of surgery to optimize visual function, cataract surgery is not free from complications that can occur after surgery such as Toxic Anterior Segment Syndrome (TASS) and Posterior Capsular Opacification (PCO). This study aims to find out how many complications occur after cataract surgery in senile cataract patients in the form of TASS and PCO at the JEC-Orbita Makassar Eye Clinic in 2022. This research is a type of quantitative research using descriptive studies. The data used is secondary data in the form of medical record data taken from the JEC-Orbita Makassar Eye Clinic. The results obtained were that a total of 64 patients suffered from TASS and PCO after cataract surgery, with 52 patients (81.25%) suffering from PCO and 12 patients (18.75%) suffering from TASS. The most common gender was female as many as 41 patients (64.07%), the most common age range was 61-75 years as many as 37 patients (57.82%), the most surgical technique used was Phacoemulsification as many as 64 patients (100%) and the highest The highest maturity before surgery was grade IV senile cataract, 39 patients (60.94%).